2015
DOI: 10.1038/srep14045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the autophagy pathway as prognostic indicators for prostate cancer

Abstract: Autophagy is a complex process of autodigestion in conditions of cellular stress, and it might play an important role in the pathophysiology during carcinogenesis. We hypothesize that genetic variants of the autophagy pathway may influence clinical outcomes in prostate cancer patients. We genotyped 40 tagging single-nucleotide polymorphisms (SNPs) from 7 core autophagy pathway genes in 458 localized prostate cancer patients. Multivariate Cox regression was performed to evaluate the independent association of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Moreover, inhibition of RHEB can lead to the suppressed proliferation of prostate cancer cell lines [16]. Previous research analyzed the relationship between genetic variants of the autophagy pathway and clinical outcomes in 458 prostate cancer patients, which indicated that high expression of ATG16L1 was correlated with lower tumor aggressiveness and favorable prognosis [17]. Fu et al reported that high expression of FAM215A was associated with low tumor grades, early disease stages, and favorable overall survival in epithelial ovarian cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of RHEB can lead to the suppressed proliferation of prostate cancer cell lines [16]. Previous research analyzed the relationship between genetic variants of the autophagy pathway and clinical outcomes in 458 prostate cancer patients, which indicated that high expression of ATG16L1 was correlated with lower tumor aggressiveness and favorable prognosis [17]. Fu et al reported that high expression of FAM215A was associated with low tumor grades, early disease stages, and favorable overall survival in epithelial ovarian cancer [18].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during tumor development, the autophagic process appears to function as a tumor suppressor and limits tumorigenesis . In this respect, it is noteworthy that a single‐nucleotide polymorphism in the promoter region of the crucial autophagy‐related gene (ATG) ATG16L1, which putatively downregulates its expression level, associated with susceptibility to thyroid and colorectal cancer and has a significant negative impact on patient survival in local and advanced metastatic prostate cancer . Further, survival of patients with advanced lung adenocarcinoma upon epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor treatment is significantly impacted by functional genetic polymorphisms in core autophagy genes, thus highlighting the potential clinical impact of autophagic signaling on cancer development and response to therapy …”
Section: Introductionmentioning
confidence: 99%
“…The autophagy lysosome pathway has been widely studied in human cancer and some genetic variants of autophagy lysosome genes were identified as associated with cancer risk or prognosis . However, no study has comprehensively and systematically evaluated the risk of germ‐line genetic variant of this pathway for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs in certain autophagy lysosome pathway genes have been shown to be associated with the risk of breast cancer, colorectal cancer (CRC), thyroid carcinoma, gastric cancer (GC), melanoma . In addition, previous studies have also assessed associations between SNPs in the autophagy lysosome pathway and clinical outcome or other clinical characteristics of patients with cancer . However, the number of the included SNPs and the samples were relatively small in most of these studies.…”
Section: Introductionmentioning
confidence: 99%